Subsurface Drip Irrigation: A Promising Solution for Maximizing Crop Yields and Water Efficiency - , Sachin, K. S, Rajavel, M., Praveen, B. R., Kadagonda Nithinkumar, Sumanth Kumar, G. V., Niranjan, B. N., Katara Akshay Rameshbhai (Archives of Current Research International, 2024)
One of the primary finite input resources for crop production in the upcoming decades for sustained food production will be irrigation water. On the other hand, there is a concern about the availability of irrigation water and its environmental and ecological sustainability. Urban activities, which are the primary sector, compete with agriculture for water as the global economy grows daily. As a result, it begs the question of whether the same amount of water utilized in irrigated agriculture can continue. It is estimated that the global population will be about 9 billion to 10 billion by 2050, and more water will be thus needed [1, 2]. Today, irrigation is the largest single consumer on the earth. Competition for water from other sectors will force irrigation to operate under water scarcity. To meet the twin challenges of conserving water and increasing the food supply, irrigated agriculture will have to improve water productivity, e.g. “more crop per drop”. The subsurface drip irrigation SDI could be an alternative to drip irrigation, which uses less water. It could save up to 25% - 50% of water regarding surface irrigation.